A new leadless pacemaker with atrioventricular synchronous pacing replacing a still working VVI leadless pacemaker: a case report. Issue 8 (15th August 2021) - Moltrasio, Massimo; Sicuso, Rita; Tundo, Fabrizio; Tondo, Claudio
Abstract: Background: A new intracardiac leadless pacemaker (ILP) has been developed to ensure atrioventricular (AV) synchrony (AVS) during ventricular pacing (VP). Recent studies have shown the feasibility and safety of accelerometer-based atrial sensing and an improvement in AVS among patients with atrioventricular block implanted with the Micra AV ILP (Medtronic Inc., Minneapolis, MN, USA). However, no data exists about the benefits of a VDD ILP in patients wearing a still working VVI Nanostim ILP (St Jude Medical, St Paul, MN, USA). We describe the feasibility of the procedure and the absence of device-related adverse events in the short-term follow-up. Case summary: We present the case of a 72-year-old man implanted with a VVI ILP (Nanostim, St Jude Medical, St Paul, MN, USA) on May 2014, who has developed symptomatic high percentage of VVI asynchronous pacing and was treated with an upgrade to synchronous AV pacemaker (PM) ILP—Micra AV (Medtronic Inc., Minneapolis, MN, USA), which has improved symptoms and functional class. Discussion: Intracardiac leadless pacemakers represent the best current option for patients requiring PM implantation who are at high risk of infection and bleeding. Our case shows that the new AVS ILP is a good alternative to VVI ILP in patients with sinus rhythm and a strong need for VP.